Overview of the Prime Health Care Performance in Albania - Kurti, Sllavka; Dollani, Petrit (Mediterranean Journal of Social Sciences, 2011)
Health is a very important aspect of human life, a fundamental human right. Even philosophically, people often refer to theconcept of health as "a goal of existence." For this reason, healthcare should be considered as an important social goal of all individuals,all sectors and all institutions of a country. "Health should be an absolute priority order, as is an 'input' essential for economicdevelopment of society." After 1990 , the Albanian health faced a degradation and a greater disorganization. From a health system,which face challenges to recovery and treatment of diseases in epidemic form, it should be transformed into a new system that will be facedwith new challenges related to the change of economic system, political opening country and its transformation into a country with marketeconomy. No doubt that this radical change brought with it many challenges, but more importantly it was to find the key to realize thefundamental transformation of the health system itself and in the context of that primary. In this regard following the establishment of theInstitute of Health Insurance, definitely the most important decision-making was to change the system of financing in the primary systemby linking funding to service providers with their performance level. This paper introduces and analyses in general the prime health carefocusing particularly on the health centers performance by analyzing different indicators. Greater difficulty in this regard was theconstruction of a scoring system, which can be measured in a realistic and objective performance level attained by the primary serviceproviders. The paper is prepared by exploring the published literature and collecting data through secondary sources. Several data sourceshave been used to describe the PHC reform as well as the HC performance in the entire territory.